Reducing Insomnia in the Elderly With Lavender Aromatherapy In Karyamulya sud-district, Kesambi District, Cirebon City : Reducing Insomnia in the Elderly With Lavender Aromatherapy - Marisa, Dewi Erna; al-Jaberi, Musheer; Elengoe, Asita; Wahyuni, Santi; Supriyadi, Yudi (Sahabat Publikasi Kuu, 2024)
Introduction: Insomnia is a problem that often occurs in elderly people, namely the inability to sleep. Management and treatment of elderly people who suffer from insomnia are broadly divided into two categories of pharmacological treatment and nonpharmacological treatment. Pharmacological treatment focuses on drug delivery. Lavender aromatherapy is a non- pharmacological intervention that can improve sleep quality in the elderly. Purpose: The aim of this research is to reduce insomnia in the elderly with Lavender aromatherapy. Methods: This type of research is quantitative with a research design using one group pretest-posttest with the pre- experimental method and paired t-test. as many as 30 elderly people aged 55-65 years and over and will be given the IRS (Insomnia Rating Scale) questionnaire which will be given before and after giving lavender aromatherapy. Respondents received lavender aromatherapy for 8 consecutive days. Results: The results showed that lavender aromatherapy had a significant effect on reducing insomnia in the elderly. Before being given lavender aromatherapy, there were 25 respondents (80.6%) with severe insomnia and 5 respondents (16.1%) with mild insomnia. After being given lavender aromatherapy, 27 respondents (90.0%) had no insomnia and 3 respondents (10.0%) had moderate insomnia. the p value is 0.00 or <0.05, thus it can be concluded that Ho is rejected and Ha is accepted. Conclusions: In administering lavender aromatherapy to the elderly in Karyamulya Village, Kesambi District, Cirebon City, there was a in the level of insomnia before and after giving lavender aromatherapy for 8 consecutive days